PENGARUH PARTISIPASI ANGGOTA TERHADAP SISA HASIL USAHA DI KOPERASI SIMPAN PINJAM MASYARAKAT BUMI PUTERA (KOMAS-BP) AMANDRAYA KABUPATEN NIAS SELATAN - Herti Diana Hutapea; Anas Tasia Pitermanis Bali (PARETO : Jurnal Riset Bisnis dan Manajemen, 2025)
The scope of this study is the effect of member participation on the remaining operating profit at the Bumi Putera Community Savings and Loan Cooperative (KOMAS-BP) Amandraya, South Nias Regency. The purpose of this study was to determine the effect of member participation on the remaining operating profit at the Bumi Putera Community Savings and Loan Cooperative (KOMAS-BP) Amandraya, South Nias Regency. The research method used was simple linear regression analysis using time series data from 2016-2018. The results showed a negative effect between member participation and the remaining operating profit. An increase of Rp. 1 in member participation will result in a decrease in the cooperative's remaining operating profit of Rp. 20,499, with other variables remaining constant, and vice versa. A decrease in member participation by Rp. 1 will result in an increase in the cooperative's remaining operating profit of Rp. 20,499.